The first record of Metacordyceps neogunnii (Metacordyceps, Clavicipitaceae) isolated from larva of Lepidoptera in Vietnam: morphological, phylogenetic characterization and chemical constituent analysis - Thuan, Lao Duc; Thuy, Le Huyen Ai; Hac, Le Cong; Mai, Nguyen Hoang; Giang, Nguyen Van; Binh Nguyen, Truong (Vietnam Journal of Biotechnology, 2022)
An entomopathogenic fungus, specimen DL0091 parasitized on the larvae of Lepidoptera, was collected from Lang Biang Biosphere Reserve, located in Lam Dong Province, Vietnam. The specimen DL0091 has been analyzed to be contained numerous chemical constituents, especially containing adenosine of 634 mg/Kg and cordycepin of 35.2 mg/Kg. Due to containing many bioactive compounds, DL0091 was promised to be a precious natural source that could be applied in fields of medicine and function food for health care. For classification, based on the morphology analysis, it was identified as Metacordyceps neogunnii (Metacordyceps, Clavicipitaceae) sharing the similar characteristics of M. neogunnii T.C. Wen & K.D. Hyde. Morphology of this species differed from Cordyceps neogunnii (Berk.) Berk., by many characteristics, such as the larger stroma of DL0091 (15–130 mm x 2–6 mm), of asci (550–680 μm × 5–8 μm), etc. Additionally, the combined multi-gene phylogenetic analysis, including ITS, Tef and Rpb1, well supported its systematic position in the clade of M. neogunnii, which was used as traditional herb in China and other Asian countries. In summary, DL0091 was identified as M. neogunnii, containing many bioactive compounds, could be used as the medicinal potential in human healthcare.